2019
DOI: 10.1016/j.atherosclerosis.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue volume is associated with premature atherosclerosis in early type 2 diabetes mellitus independent of traditional risk factors

Abstract: Visceral adipose tissue volume is associated with premature atherosclerosis in early type 2 diabetes mellitus independent of traditional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
(44 reference statements)
1
27
0
1
Order By: Relevance
“…7 There is a positive correlation between the volume of visceral fat tissue in patients with T2DM and arterial inflammation. 8 Another study demonstrated that metabolic syndrome is associated with increased arterial stiffness in patients with T2DM, and abdominal obesity is associated increased arterial stiffness. 9 Obesity and diabetes are risk factors for cardiovascular disease, and cardiovascular risk increases when both factors coexist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 There is a positive correlation between the volume of visceral fat tissue in patients with T2DM and arterial inflammation. 8 Another study demonstrated that metabolic syndrome is associated with increased arterial stiffness in patients with T2DM, and abdominal obesity is associated increased arterial stiffness. 9 Obesity and diabetes are risk factors for cardiovascular disease, and cardiovascular risk increases when both factors coexist.…”
Section: Introductionmentioning
confidence: 99%
“…9 Obesity and diabetes are risk factors for cardiovascular disease, and cardiovascular risk increases when both factors coexist. [8][9][10] Therefore, preventing T2DM in obesity is critical issue for preventing cardiovascular complications. T2DM is a progressive disease with a course that typically depends on β-cell dysfunction…”
Section: Introductionmentioning
confidence: 99%
“…In men, the most common form of obesity is central or abdominal obesity, and consists of an accumulation of visceral adipose tissue (64). According to various studies, this type of obesity has been associated, with a higher risk of diseases such as insulin resistance, type 2 diabetes, and cardiovascular risk (65)(66)(67) are ROS generated by inflammatory pathways, adipokine increased levels (leptin) and leukocyte infiltration in white adipose tissue (59). In isolated adipocytes, it was reported that TNF-α suppresses insulin signal transduction and expression of the insulin receptor, leading to hyperglycemia, and even to pancreatic β-cell destruction.…”
Section: Adipose Tissues As An Endocrine Organmentioning
confidence: 99%
“…Recently, as a variable clinical manifestation, fat accumulation in the visceral organs harboring genetic polymorphism was considered as a subtype of NAFLD without obesity [6]. Regardless of obesity, visceral adipose tissue (VAT) is associated with MetS and T2D [7]. Specifically, VAT is associated with the degree of hepatic fat infiltration, even in non-obese adults [8].…”
Section: Introductionmentioning
confidence: 99%